2001
DOI: 10.1021/bi0104571
|View full text |Cite
|
Sign up to set email alerts
|

Acid−Base Catalysis by UDP-Galactose 4-Epimerase:  Correlations of Kinetically Measured Acid Dissociation Constants with Thermodynamic Values for Tyrosine 149

Abstract: The steady-state kinetic parameters for epimerization of UDP-galactose by UDP-galactose 4-epimerase from Escherichia coli (GalE), Y149F-GalE, and S124A-GalE have been measured as a function of pH. The deuterium kinetic isotope effects for epimerization of UDP-galactose-C-d(7) by these enzymes have also been measured. The results show that the activity of wild-type GalE is pH-independent in the pH range of 5.5-9.3, and there is no significant deuterium kinetic isotope effect in the reaction of UDP-galactose-C-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 25 publications
4
37
0
3
Order By: Relevance
“…2). The kinetic parameters determined from these data (Table 1) are similar to those published for human GALE and for GALEs from other species [21,27,29,30]. There is no evidence that human GALE is glycosylated in vivo, and there is no anomalous migration of recombinant human GALE produced in yeast [27], and thus the observed activity probably reflects that of the native enzyme.…”
Section: Expression and Purification Of Human Galesupporting
confidence: 70%
“…2). The kinetic parameters determined from these data (Table 1) are similar to those published for human GALE and for GALEs from other species [21,27,29,30]. There is no evidence that human GALE is glycosylated in vivo, and there is no anomalous migration of recombinant human GALE produced in yeast [27], and thus the observed activity probably reflects that of the native enzyme.…”
Section: Expression and Purification Of Human Galesupporting
confidence: 70%
“…35 Further analysis of the available eGalE structures and spectrophotometric studies revealed a pHdependent charge transfer complex between Tyr149 and NAD. 44 Kinetic experiments with E. coli GalE and its S124A variant confirmed that tyrosine is the base catalyst for hydride transfer. 43,44 In the next step of the mechanism, the transient keto-sugar is retained in the active site by anchoring of the substrate by its UDPgroup while the 4 0 -ketopyranose intermediate undergoes a rotation in the active site.…”
Section: Mechanismmentioning
confidence: 87%
“…44 Kinetic experiments with E. coli GalE and its S124A variant confirmed that tyrosine is the base catalyst for hydride transfer. 43,44 In the next step of the mechanism, the transient keto-sugar is retained in the active site by anchoring of the substrate by its UDPgroup while the 4 0 -ketopyranose intermediate undergoes a rotation in the active site. Finally, the reverse of the first step occurs, namely the transfer of the hydride back to the C4 of the sugar.…”
Section: Mechanismmentioning
confidence: 87%
“…This movement means that the re-reduction reaction is not stereospecific and thus the products are a mix of C-4 isomers (19,20). The redox reaction is facilitated by a tyrosine residue (Tyr-157 in the human enzyme) acting as an active site base (13,21). The bacterial enzyme is highly specific for UDPgalactose, whereas the human enzyme can also catalyse the interconversion of UDP-N-acetylgalactosamine and UDP-Nacetylglucosamine.…”
Section: Udp-galactose 4-epimerasementioning
confidence: 99%